PENGARUH KEBIJAKAN CORPORATE SOCIAL RESPONSIBILITES TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2016) - Dhafi Rahmatul Ikma; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
The aim of this study is determine the effect of corporate social responsibility (CSR) on accounting conservatism, and the effect of corporate social responsibility (CSR) on accounting conservatism with state ownership as a moderating variable. This research uses cash flow, firm age, and investment cycle as control variables.This study uses secondary data from annual financial reports on non-financial companies listed on the Indonesian stock exchange in 2016. The method in selecting samples is using the purposive sampling method. The total sample from this study is 204 samples. This study uses multiple regression analysis to test the hypothesis.The results of this study indicate that social responsibility (CSR) has a positive effect on the level of accounting conservatism which shows that the government-mandated CSR policies are sufficient to encourage conservative financial reporting. However, due to the possibility of political affiliation, the interaction between CSR and state ownership (BUMN) does not affect the level of accounting conservatism.